Sanitasi rumah dan stunting di Wilayah Kerja Puskesmas Labuan Kabupaten Donggala - Christine Christine; Fellysca Veronica Margareth Politon; Fahmi Hafid (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
Poor home sanitation can increase the risk of stunting in children. The study aims to analyze the risk factors for stunting based on house conditions, sanitation facilities, and occupant behavior. Observational research using a case-control study design was carried out in September–December 2020. The sample size was 60 toddlers (30 cases and 30 controls) taken randomly by simple arithmetic. Case samples are stunted toddlers based on e-PPGBM data. The control sample is a typical toddler who is the closest neighbor to the case with age equivalence. Respondents were mothers of toddlers. Data on the physical condition of the house and sanitation facilities were obtained through direct observation, while data on the behavior of the house occupants were obtained through interviews. Data processing was carried out by cleaning and editing, coding for categorical variables, entry and data processing. Data were analyzed using the Chi-square test and odds ratio at 95% CI. The house's physical condition (p= 0,058; OR= 8,83) and the behavior of the householder in managing sanitation are risk factors for stunting (p= 0,002; OR= 6,91). In conclusion, toddlers who live in houses with physical conditions that do not meet health requirements are at risk of experiencing stunting 8,83 times. Residents of houses whose behavior does not meet sanitation requirements risk 6,91 times experiencing stunting in toddlers.